Erosion and screening of tungsten during inter/intra-ELM periods in the JET-ILW divertor. (December 2020) - Huber, A.; Brezinsek, S.; Huber, V.; Sertoli, M.; Sergienko, G.; Borodkina, I.; Baruzzo, M.; Kirschner, A.; Borodin, D.; Mailloux, J.; Aleiferis, S.; Carvalho, P.; et al.
Abstract: Intra-ELM tungsten sources, which dominate the total W source, are quantified in the inner and outer divertor of JET-ILW. The amount of the sputtered W atoms for individual ELMs demonstrates a clear dependence on the ELM frequency. It decreases when the pedestal temperature is lower and, correspondingly, the ELM frequency is higher. Nevertheless, the entire gross erosion W source (the number of eroded W atoms per second due to ELMs) increases initially with ELM frequency and reaches its maximum at fELM  ≈ 50–55 Hz followed by its reduction in the high frequency range. The in/out asymmetry of the intra-ELM W sources during ELMs is a critical issue and is investigated in this contribution. At a lower ELM frequency of about 35 Hz the outer divertor gross W source is larger by a factor of 1.5. However the in/out asymmetry of the W erosion decreases strongly with ELM frequency demonstrating a nearly symmetric W source in both divertor legs at frequencies above 70 Hz. The screening of tungsten in the open magnetic configuration with strike points on tile 5 is more efficient by a factor of about 1.7 than in the corner configuration with the outer strike point at the pumping duct entrance.